2007
DOI: 10.1007/s11064-007-9466-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic N-Acetyl Cysteine Administration on Oxidative Status in the Presence and Absence of Induced Oxidative Stress in Rat Striatum

Abstract: Antioxidants have possible therapeutic value in neurodegenerative disorders, although they may have pro-oxidant effects under certain conditions. Glutathione (GSH) is a key free radical scavenger. N-acetylcysteine (NAC) bolsters GSH and intracellular cysteine and also has effective free radical scavenger properties. The effects of chronic NAC administration (50 mg/kg/day, 500 mg/kg/day, 1500 mg/kg/day x 21 days) on cellular markers of oxidative status was studied in striatum of healthy male Sprague-Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…Interestingly, in several in vivo studies, a high dose of NAC was found to act as a pro-oxidant rather than an antioxidant. High doses of NAC were found to be pro-oxidative in function in healthy rat striatum (48). Similarly, a low dose of NAC protected rats against endotoxin-mediated oxidative stress, whereas a high dose increased their mortality presumably because of its pro-oxidant action (49).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in several in vivo studies, a high dose of NAC was found to act as a pro-oxidant rather than an antioxidant. High doses of NAC were found to be pro-oxidative in function in healthy rat striatum (48). Similarly, a low dose of NAC protected rats against endotoxin-mediated oxidative stress, whereas a high dose increased their mortality presumably because of its pro-oxidant action (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clozapine, olanzapine, and to a lesser extent risperidone, were able to reverse the changes induced by haloperidol (Pillai et al, 2007). Haloperidol-induced oxidative stress parameters in rats have also been shown to be ameliorated by the antioxidant drug, Nacetylcysteine (NAC) (Harvey et al, 2007). In-vitro cell studies have demonstrated a protective effect of atypicals, such as olanzapine and quetiapine, on PC12 cells exposed to oxidative stress Wei et al, 2003).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…We have previously reported that excess of VLCFA decreases reduced glutathione, and X-ALD cells are more sensitive to glutathione depletion (20). N-acetylcysteine was chosen, because it can regenerate reduced glutathione (GSH) and scavenge several ROS species including OH $ , H 2 O 2 , peroxyl radicals, and nitrogen-centered free radical (28). a-lipoic acid (LA) was chosen, as it can regenerate GSH from its oxidized counterpart (GS-SG) (3), thus enhancing the effects of NAC.…”
Section: A Combination Of Antioxidants Prevents Oxidative Stress and mentioning
confidence: 99%